Population genetics and plant growth experiments as prerequisite for conservation measures of the rare European aquatic plant Luronium natans (Alismataceae) - Makuch, Weronika A.; Wanke, Stefan; Ditsch, Barbara; Richter, Frank; Herklotz, Veit; Ahlborn, Julian; Ritz, Christiane M. (Frontiers in Plant Science, 2023)
Information provided by population genetic studies is often necessary to effectively protect endangered species. In general, such data is scarce for aquatic plants and this holds also for Luronium natans, an aquatic macrophyte endemic to northwestern and western Europe. It is threatened across its whole distribution range due to human influences, in particular due to eutrophication and intensive fish farming. Inspite of habitat protection populations continue to decline and re-introductions are one possibility to prevent the species’ extinction. Therefore, insights in genetic diversity and relatedness of source populations is warranted and thus we performed Amplified Fragment-Length Polymorphism (AFLP) on two large populations in Saxony, Germany (Großenhainer Pflege and Niederspree), complemented with numerous additional occurences from Europe. In addition, we conducted experiments on plant growth to assess optimal conditions for ex-situ cultivation taking water temperature, water level and substrate into account. We revealed considerably high levels of genetic diversity within populations (Shannon Indices ranged from 0.367 to 0.416) implying that populations are not restricted to clonal growth only but reproduce also by open-pollinated flowers. Remarkably, the two geographically close Saxon populations were genetically distant to each other but subpopulations within a locality were completely intermingled. Concerning optimal cultivation conditions, longest roots were obtained at temperatures > 14°C and saturated, but not submerging water levels. Thus, our findings advocate for a re-introduction scheme from nearby source populations and provide detailed information on successful ex-situ cultivation.